2018
DOI: 10.4269/ajtmh.18-0386
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Late Presentation to HIV care in a South Indian Cohort

Abstract: Late presentation to healthcare by HIV infected patients' is common in India despite access to free combination antiretroviral therapy (cART). We assessed risk factors for late presentation among patients with a recent HIV diagnosis in an academic university-based antiretroviral treatment center. This retrospective study included 474 recently diagnosed HIV-infected patients registered for cART between 2012 and 2013. Subjects with CD4 T-lymphocyte (CD4) count ≤ 350 cells/μL or with an AIDS defining event were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(43 reference statements)
1
1
0
1
Order By: Relevance
“…Although women are, in Africa, more vulnerable to acquiring HIV, in this study, we found that men were more likely to have late presentations, compared with women. Similar results were found in previous studies carried out in South Africa [19], India [24], sub-Saharan Africa [25], Switzerland [26], Asia [27], Ethiopia [28], Benin [29], and Asia [15].…”
Section: Discussionsupporting
confidence: 92%
“…Although women are, in Africa, more vulnerable to acquiring HIV, in this study, we found that men were more likely to have late presentations, compared with women. Similar results were found in previous studies carried out in South Africa [19], India [24], sub-Saharan Africa [25], Switzerland [26], Asia [27], Ethiopia [28], Benin [29], and Asia [15].…”
Section: Discussionsupporting
confidence: 92%
“…A análise do perfil sociodemográfico da amostra evidenciou características semelhantes a outros estudos que avaliaram mulheres com HIV (14)(15)(16) , com predomínio da faixa etária 20-30 anos, raça parda, em união estável, com ensino regular completo e donas de casa. Diante da feminização da epidemia do HIV, fatores socioeconômicos podem atuar como determinantes para a infecção, já que grande parte das mulheres infectadas ainda se encontra em idade fértil (14) , possui menor nível de escolaridade, vive em união estável (17) , é parda (18) e dona de casa (19) .…”
Section: Discussionunclassified
“…The analysis of the sociodemographic profile of the sample showed characteristics similar to other studies that evaluated women with HIV ( 14 , 15 , 16 ) ; predominance of the age group 20-30 years, mixed race, in a common-law marriage, complete regular education and housewives. Given the feminization of the HIV epidemic, socioeconomic factors can act as determinants for the infection, since most infected women were still of childbearing age ( 14 ) , in a common-law marriage ( 17 ) , mixed race ( 18 ) , housewives ( 19 ) and have a low level of education.…”
Section: Discussionmentioning
confidence: 99%